Identifying high-mobility tetracene derivatives using a non-adiabatic molecular dynamics approach. Issue 3 (12th December 2019) - Ziogos, Orestis George; Giannini, Samuele; Ellis, Matthew; Blumberger, Jochen
Abstract : Alkylated tetracenes offer an attractive route towards flexible columnar organic electronics applications with unprecedented hole mobilities and robust charge transfer mechanisms. Abstract : The search for conductive soft matter materials with significant charge mobility under ambient conditions has been a major priority in organic electronics (OE) research. Alkylated tetracenes are promising cost-effective candidate molecules that can be synthesized using wet chemistry methods, resulting in columnar single crystals with pronounced structural stability at and above room temperature. A remarkable characteristic of these materials is the capability of tuning the tetracene core intracolumnar stacking pattern and the crystal melting point via the side chain length and type modifications. In this study, we examine the performance of a series of alkylated tetracenes as hole conducting materials using a novel atomistic simulation technique that allows us to predict both the charge transport mechanism and mobilities. Our simulations demonstrate that molecular wires of alkylated tetracenes are capable of polaronic hole conduction at room temperature, with mobility values ranging up to 21 cm 2 V −1 s −1, thus rendering such materials a highly promising choice for flexible OE applications. As regards the charge transfer robustness, two promising tetracene derivatives are identified with the capability of seamless inter-wire polaron delocalization, alleviating possible transfer bottlenecks due to local molecular defects. Our findings suggest that alkylated tetracenes offer an attractive route towards flexible columnar OE materials with unprecedented hole mobilities.